To study the relation between spontaneous bacterial peritonitis and serum ascitis albumin gradient in chronic liver disease patients - Verma, Rajendra Kumar; Giri, Richa; Agarwal, Mayuri; Srivastava, Vaibhav (International Journal of Research in Medical Sciences, 2017)
Background: About half the patients with cirrhosis develop ascites during 10 years of observation. The present study was designed to study the relation between spontaneous bacterial peritonitis and serum ascites albumin gradient in chronic liver disease patients. Methods: This prospective observational study was done in 55 patients with chronic liver disease attending IPD of tertiary hospital. Based on investigation findings, patients were divided into two groups: Group A-Patients with sterile cirrhotic ascites, Group B- Patients with spontaneous bacterial peritonitis. Detailed history, examination and relevant investigation were done. Data was collected, recorded and statistical calculation was done using in Microsoft excel 2007. Results: Most common presenting symptoms of SBP patients were increasing ascites refractory to treatment (90%), followed by peripheral edema (80%). Jaundice and hepatic encephalopathy was found in 75% and 65% respectively. Serum and ascites albumin levels were lower in Group B (2.54±0.33 and 0.43±0.23 g/dl respectively) as compared to Group A (2.85±0.36 and 0.91±0.31 g/dl respectively) and it was statistically significant. The Mean±SD of SAAG for group A and group B was (1.94±0.36) and (2.09±0.47 g/dl) respectively. This difference was statistically not significant. Conclusions:Study conclude that the development of spontaneous bacterial peritonitis in chronic liver disease patients with sterile ascites is directly proportional to ascitic fluid albumin and serum albumin concentration whereas occurrence of SBP is not affected by variation in SAAG ratio if it is already higher than 1.1 g/dl.